Deciphering the role of tRNA-derived fragments in neurological and psychiatric disease pathogenesis - Kocakusak, Huseyin; Kök, Aysu Başak; Ozturk, Bilgesu; Karacicek, Bilge; Genc, Sermin (Frontiers in Cellular Neuroscience, 2025)
tRNA-derived small RNAs (tsRNAs) have recently gained attention as important regulatory non-coding RNAs (ncRNAs). Among these, tRNA-derived fragments (tRFs) constitute a distinct and well-defined subset. These small molecules play essential roles in maintaining cellular homeostasis and have been increasingly implicated in disease pathogenesis. This comprehensive review specifically concentrates on tRFs, takes a closer look at their diverse mechanisms of action and their impact on key cellular processes. Specific focus is placed on their functions within the central nervous system (CNS) and their involvement in the molecular pathways driving neurological diseases and neurodevelopmental disorders. Besides their pathological roles, the review covers fundamental aspects of tRFs, including their biogenesis, classification, and structural features. It also describes latest methods for tRFs detection, prediction, and validation. Overall, the review points out the ongoing need for research in this area, especially when it comes to applying these findings clinically. Importantly, it highlights their potential as useful biomarkers and even targets for treatment in neurological diseases.